Pengaruh Model Problem Based Learning Berbantuan Permainan Monopoli Terhadap Kemampuan Berpikir Kritis Siswa SD dalam Pembelajaran IPS - Rizqiana, Rifka Nur; Ani Nur Aeni; Dety Amelia Karlina (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to analyze the effect of the Problem Based Learning model assisted by monopoly games on the critical thinking skills of elementary school students in social studies learning. The research approach used is quantitative with a quasi-experimental research method designed as a Nonequivalent Control Group Design. The instruments and data collection techniques used in this research are test questions. The results of the study show 1) there is a positive influence of the Problem Based Learning model assisted by monopoly games on students' critical thinking skills, with a mean difference result from the pretest and posttest data of sig. 0.000<0.05.2) There is a positive influence of the conventional learning model on students' critical thinking skills, with an average difference from pretest and posttest data of sig. 0.000<0.05. 3) There is a significant difference in influence between the experimental class and the control class. The N-Gain test results indicate that there is an improvement in students' critical thinking skills in the experimental class with a moderate category using the Problem Based Learning model assisted by Monopoly games, and a low category improvement in the control class using conventional learning. Thus, the Problem Based Learning model assisted by Monopoly games has an impact on the critical thinking skills of elementary school students in social studies learning.